Reduction of polycyclic aromatic hydrocarbons concentrations in smoked guinea fowl (Numida meleagris) meat using gamma irradiation - Evelyn A. Otoo; Fidelis C.K. Ocloo; Victoria Appiah; Christian Nuviadenu; Anita Asamoah (CyTA - Journal of Food, 2022)
This study investigated the effect of gamma irradiation on polycyclic aromatic hydrocarbons (PAHs) contents in smoked guinea fowl meat. Guinea fowls were processed, smoked and irradiated at 0, 2.5, 5.0 and 7.5 kGy. PAHs were extracted and their concentrations determined using Gas Chromatography-Mass Spectrometer. Health risk of the PAHs to humans was also estimated. Sixteen PAHs were detected in the smoked meat with concentrations ranging from 0.002 to 9.221 μg/kg. B[a]P recorded the highest value of 9.221 μg/kg (0 kGy) and the least value of 0.057 μg/kg for the meat samples. Irradiation significantly reduced the PAHs concentrations and their carcinogenic derivatives. Health risk estimation suggested that the levels of PAHs in the treated smoked meats pose no dietary intake risks. Gamma irradiation has the potential to minimize the toxicity of carcinogenic PAHs in smoked guinea fowl meat, thereby increasing export and enhancing the future economical marketing of this food product.